A novel desmin mutation leading to autosomal recessive limb-girdle muscular dystrophy: distinct histopathological outcomes compared with desminopathies. Issue 7 (18th May 2013) - Cetin, Nilgun; Balci-Hayta, Burcu; Gundesli, Hulya; Korkusuz, Petek; Purali, Nuhan; Talim, Beril; Tan, Ersin; Selcen, Duygu; Erdem-Ozdamar, Sevim; Dincer, Pervin
Abstract : Background: Autosomal recessive limb girdle muscular dystrophy (LGMD2) is a heterogeneous group of myopathies characterised by progressive muscle weakness involving proximal muscles of the shoulder and pelvic girdles including at least 17 different genetic entities. Additional loci have yet to be identified as there are families which are unlinked to any of the known loci. Here we have investigated a consanguineous family with LGMD2 with two affected individuals in order to identify the causative gene defect. Methods and results: We performed genome wide homozygosity mapping and mapped the LGMD2 phenotype to chromosome 2q35–q36.3. DNA sequence analysis of the highly relevant candidate gene DES revealed a homozygous splice site mutation c.1289-2A>G in the two affected family members. Immunofluorescent staining and western blot analysis showed that the expression and the cytoskeletal network formation of mutant desmin were well preserved in skeletal muscle fibres. Unlike autosomal dominant desminopathies, ultrastructural alterations such as disruption of myofibrillar organisation, formation of myofibrillar degradation products and dislocation/aggregation of membranous organelles were not present. This novel splice site mutation results in addition of 16 amino acids within the tail domain of desmin, which has been suggested to interact with lamin B protein. We also detected a specific disruption of desmin-lamin B interaction in the skeletal muscle of the patient by confocal laser scanning microscopy. Conclusions: Our study reveals that autosomal recessive mutations in DES cause LGMD2 phenotype without features of myofibrillar myopathy.